2017
DOI: 10.1111/eci.12867
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‐145 regulates disabled‐2 and Wnt3a expression in cardiomyocytes under hyperglycaemia

Abstract: Aims: MicroRNA-145 (miR-145) could protect cardiomyocyte apoptosis against oxidative stress and repair infarcted myocardium. Angiotensin II (Ang II), a proinflammatory cytokine could modulate myocardial remodelling. However, the role of hyperglycaemia on miR-145 expression in cardiomyocyte or diabetes is not known. The effect of Ang II on miR-145 expression under hyperglycaemia in cardiomyocytes remains unknown. We sought to investigate the effect of hyperglycaemia and Ang II on miR-145 expression in cardiomyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In this study, the results of bioinformatics analysis predicted that miR-145 might contain the binding sites with MEG3, and this prediction was further proved by the experimental validation. Consistent with the findings of Wang et al [17], we also observed the reduction of miR-145 expression in HG-treated AC16 cells, and this reduction was overturned by MEG3 knockdown.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the results of bioinformatics analysis predicted that miR-145 might contain the binding sites with MEG3, and this prediction was further proved by the experimental validation. Consistent with the findings of Wang et al [17], we also observed the reduction of miR-145 expression in HG-treated AC16 cells, and this reduction was overturned by MEG3 knockdown.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, miR-145 was reported to be associated with hyperglycemia in diabetes. 36 Thus, reduced plasma miR-145 levels observed in our patient samples may be related to increased fasting blood glucose levels. In contrast, miR-410 may be more closely related to plasma cholesterol level.…”
Section: Mir-377 Reduces Triglyceride Levels Through the Dnmt1-gpihbpmentioning
confidence: 74%
“…Compared to its homologue, Wnt3a is known to regulate the pathogenesis of T2DM from several processes but its role is controversial. Under the similar hyperglycaemia condition in STZ‐induced diabetic rat, Wnt3a/β‐catenin pathway was found to be inhibited in cardiomyocytes, 43 but swimming exercise was proved to alleviate insulin resistance through inhibiting the overactivated Wnt3a/β‐catenin pathway in skeletal muscles. 44 Wnt3a is an important modulator of the differentiation and maturation of β‐cells, overexpressing Wnt3a promotes the proliferation of porcine pancreatic stem cells (PSCs), which are valuable in transplantation application of T2DM.…”
Section: Roles Of Wnts In T2dm and Related Complicationsmentioning
confidence: 99%